Alleviating mass transfer limitations in industrial external-loop syngas-to-ethanol fermentation. (21st September 2022) - Puiman, Lars; Abrahamson, Britt; Lans, Rob G.J.M. van der; Haringa, Cees; Noorman, Henk J.; Picioreanu, Cristian
Graphical abstract: Highlights: Detailed analysis on gas transfer rate in industrial syngas fermentation. CFD reveals mass transfer limitation topography in external-loop gas-lift reactors. Bubbles smaller than 2 mm are key to reach required mass transfer capacities. The produced ethanol minimizes bubble size and increases gas hold-up. Transport limitations in air–water systems can be alleviated in syngas fermentation. Abstract: Mass transfer limitations in syngas fermentation processes are mostly attributed to poor solubility of CO and H2 in water. Despite these assumed limitations, a syngas fermentation process has recently been commercialized. Using large-sale external-loop gas-lift reactors (EL-GLR), CO-rich off-gases are converted into ethanol, with high mass transfer performance (7–8.5 g.L -1 .h −1 ). However, when applying established mass transfer correlations, a much poorer performance is predicted (0.3–2.7 g.L -1 .h −1 ). We developed a CFD model, validated on pilot-scale data, to provide detailed insights on hydrodynamics and mass transfer in a large-scale EL-GLR. As produced ethanol could increase gas hold-up (+30%) and decrease the bubble diameter (≤2 mm) compared to air–water mixtures, we found with our model that a high volumetric mass transfer coefficient (650–750 h −1 ) and mass transfer capacity (7.5–8 g.L -1 .h −1 ) for CO are feasible. Thus, the typical mass transfer limitations encountered in air–water systems can be alleviated in the syngas-to-ethanol fermentation process.